Comparison as a teaching method within social work training at a University of Applied Science - Uecker, Horst (Swiss Journal of Educational Research, 2018)
The following article, based on the theory of observation, discusses the assumption that a systematic introduction of comparison as teaching method is worthwhile within social work vocational training at a University of Applied Science. This approach should foster students’ reflective attitude, while counteracting the pervading habit they have to play off practice against theory.